Industri Film: Pemetaan Strategi Percepatan Ekonomi Kreatif Nasional Menuju Indonesia Maju 2040 - Sintowoko, Dyah Ayu Wiwid (Institut Seni Indoensia Surakarta, 2023)
The focus on the Indonesian film industry's progress is just a mare centered on financial assistance for film appreciation and preparation for film production. This research was carried out because of critical thinking about the Indonesian film industry, which is now the time for a more structured design phase. This is because competition for foreign films, such as Korean films, is still fierce. To stem the high interest in foreign products in the country, a filter such as a well-thought-out design is required to map the direction of Indonesian film. As a result, this study intends to produce an outcome mapping the master plan for accelerating the creative economy in the film industry based on historical klasters phases 1.0 to 4.0. The method employed is analytical descriptive, with a film literature study approach. The study's findings indicate that progress in the film industry can be made from the ground up, such as through collaboration between government agencies and education, which complement each other. Mapping based on phases 1.0 to 4.0 is also intended to serve as the foundation for the proposed mapping of the pattern of the Indonesian film industry. The strategy adapted from Korean Cultural Industry as well.